PERAN JOB SATISFACTION DALAM MEMDIASI KECERDASAN EMOSIONAL, TEAMWORK DAN ADAPTABILITAS TERHADAP KINERJA KARYAWAN PADA DPUPP UPT PENGELOLA JALAN PANJI KABUPATEN SITUBONDO - Wahyu Candra Wijaya; Mohammad Yahya Arief; Rini Kartika Sari (Fakultas Ekonomi dan Bisnis, 2026)
This study aims to examine the role of Job Satisfaction as a mediating variable in the relationship between Emotional Intelligence, Teamwork, and Adaptability and Employee Performance at DPUPP UPT Road Management Panji, Situbondo Regency. The sampling technique employed in this research was saturated sampling, involving a total of 33 respondents. Data analysis was conducted using SmartPLS 3.0. The analytical methods applied included convergent validity testing, reliability testing, classical assumption testing, goodness of fit (GOF) testing, coefficient of determination analysis, structural equation modeling (inner model analysis), and hypothesis testing.The results of the direct-effect hypothesis testing indicate that Emotional Intelligence does not have a significant effect on Job Satisfaction, Teamwork does not have a significant effect on Job Satisfaction, and Adaptability does not have a significant effect on Job Satisfaction. Furthermore, Emotional Intelligence has a significant effect on Employee Performance, while Teamwork and Adaptability do not have significant effects on Employee Performance. In addition, Job Satisfaction has a significant effect on Employee Performance. The results of the indirect-effect hypothesis testing reveal that Emotional Intelligence does not significantly influence Employee Performance through Job Satisfaction as a mediating variable. Similarly, Teamwork does not significantly influence Employee Performance through Job Satisfaction as a mediating variable, and Adaptability does not significantly influence Employee Performance through Job Satisfaction as a mediating variable.